Formation of Cultural Immunity to Mass Culture in Adolescent Students in Our Country and Abroad - Aripov Shokirjon Olimovich (European International Journal of Pedagogics, 2025)
This article discusses the use of gender strategies in the formation of cultural immunity against "mass culture" in adolescents, and it is recognized that there are attempts to interpret "mass culture" as a cultural phenomenon in leading higher educational institutions of the world.